Strategies for Ethics Education with Health Profession Students Before, During, and After Placements - Pollard, Natalie; Nisbet, Gillian; Kenny, Belinda; Sheepway, Lyndal; Jacobson, Jodie; Tartakover, Emily; Kilgour, Andrew; McAllister, Lindy (International Journal of Practice-based Learning in Health and Social Care, 2018)
Health professionals must practice ethically in order to ensure compassionate and effective client care; function as good interdisciplinary team members; and protect themselves from litigation, and conduct and ethics complaints. Ethics education is a routine inclusion in health profession degrees, but may only be taught in the classroom, divorced from practice. This article argues that students need ethics education before, during, and after practice placements. We suggest that many powerful opportunities for teaching ethics on and after placements are missed or under-utilised. We have reviewed the scant evidence, and the literature more broadly, to identify strategies for teaching ethics before, during, and after placements; and have added strategies drawn from our own experiences as clinical educators. We highlight where interdisciplinary perspectives can be added to ethics education. We conclude that more research is needed into approaches and strategies for teaching ethics in different contexts.